Malmvagnslock : Framtagning av ett öppningssystem till ett lock tillhörande logistiksystemet Turn Dumper - Hägg, Malin; Silfver, Lotta (2015)
This report presents a Master Thesis in Industrial Design Engineering performed by two students at Luleå University of Technology, and it comprises 30 credits over a period of 20 weeks during the spring of 2015. The thesis describes a development project of a roof solution to a new railroad based logistics system called Turn Dumper, developed by Kiruna Wagon. The Turn Dumper wagon requires a cover since it has a closed bottom and no drains, and it is thus important to protect the bulk material from precipitation and prevent it from dusting out. The main premise for the cover is that it must be adapted to the Turn Dumper unloading station and wagon as well as enable loading with both wheel loader and silo. Further it is important that the opening and closing process of the cover can be performed in a safe manner with respect to the system as well as the user. To ensure that freight transport by the Turn Dumper system can be performed safely, the roof solution should have a locking mechanism to keep it closed. The process used in this project is a customised version of Kiruna Wagon’s own routine for product development. In addition to this routine, Kiruna Wagon has implied Lean Product Development in their work process and therefore Lean has been a basis for this thesis as well. The process this project has followed is divided into five steps; planning, literature review, feasibility study, creativity and realisation respectively final product development. During the feasibility study were, amongst others, benchmarking and user studies used to find the needs for a roof solution to Turn Dumper and from these be able to state a requirement specification. In the creativity and realisation phase different creative methods were used to generate as many concepts as possible. Thereafter the concepts were evaluated and the number of concepts was reduced until only one concept remained. This concept was detailed design in the final product development phase and the result for the Turn Dumper roof solution is a two-piece ...